2017
DOI: 10.1080/14036096.2017.1284154
|View full text |Cite
|
Sign up to set email alerts
|

Equity Inequity: Housing Wealth Inequality, Inter and Intra-generational Divergences, and the Rise of Private Landlordism

Abstract: There is much evidence of rising inequalities across advanced economies. This paper argues for the special position of housing equity in inequality dynamics while challenging a persistent "ideology of mass homeownership" as a widespread and equalizing mechanism of asset accumulation. Contemporary dynamics of diminished homeownership access contrast to the continued attractiveness of real estate among those with capital and recent growths in private landlordism. The research presents an explorative examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(108 citation statements)
references
References 54 publications
4
99
0
5
Order By: Relevance
“…One of the first studies to show this longitudinal decline was Forrest et al (2003), for Japan. Among other national case-study examples, Kurz & Blossfeld (2004) have found the same trend for France, Denmark and Spain, Yates & Bradbury (2010) for Australia, and both Arundel (2017) and Udagawa & Sanderson (2017) for the United Kingdom. In all these countries, younger people have for some time now been entering homeownership in relatively smaller numbers.…”
Section: Key Relevant Findings Of Existing Literaturementioning
confidence: 83%
See 1 more Smart Citation
“…One of the first studies to show this longitudinal decline was Forrest et al (2003), for Japan. Among other national case-study examples, Kurz & Blossfeld (2004) have found the same trend for France, Denmark and Spain, Yates & Bradbury (2010) for Australia, and both Arundel (2017) and Udagawa & Sanderson (2017) for the United Kingdom. In all these countries, younger people have for some time now been entering homeownership in relatively smaller numbers.…”
Section: Key Relevant Findings Of Existing Literaturementioning
confidence: 83%
“…177-178), developments of the new millennium have largely disabused researchers of this view. The ownership of housing, which tends to be the largest component of household wealth in such societies, has over the past two decades become increasingly concentrated (Appleyard & Rowlingson, 2010;Arundel, 2017;Di, 2005); and, crucially, housing wealth tends to be closely correlated with other types of wealth (e.g. Department for Communities and Local Government, 2010).…”
Section: Key Relevant Findings Of Existing Literaturementioning
confidence: 99%
“…New housing market dynamics and tenure preferences could promote stronger orientation towards urban centres. More broadly, a discursive and practiced shift away from (or delay of) homeownership among certain groups has potentially important implications towards unequal patterns of wealth accumulation in the long-run (Arundel 2017). Lastly, the analysis also emphasizes the importance of how specific cultural, economic and housing contexts frame discourses surrounding tenure and lifecourse transitions.…”
Section: Discussionmentioning
confidence: 99%
“…This is complimented by digital developments which have facilitated managing diverse and scattered housing portfolios (Fields, 2019;Mills et al, 2019). Alongside institutional players, we see a cohort of homeownerspredominantly olderhaving accumulated substantial (housing) wealth, able to mobilize their assets to acquire additional property to rent out (Arundel, 2017;Ronald & Kadi, 2018). This can be as a commercial activity to supplement retirement income, but also a basis for intergenerational support on the housing market.…”
Section: A Revival Of Private Rentingmentioning
confidence: 99%
“…These studies have theorized this development, often from a political-economy perspective. They cite macro-economic developments such as historically low interest rates, deregulatory housing policies and wealth concentration among already affluent households as drivers of increased investment in rental housing, embedded within a broader framework of housing financialization (Arundel, 2017;Fields, 2018;Kemp, 2015;Leyshon & French, 2009). Other studies highlight the growing demand for private-rental housing from specific population groups unable to afford the structurally inflated prices for homeownership (Coulter, 2017;Lennartz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%